Antidiarrheal characteristics of tempe produced traditionally and industrially in children aged 6-24 months with acute diarrhea - Yati Soenarto; Sudigbia I; Herman Herman; Karmini M; Karyadi D (Indonesian Pediatric Society, 2001)
A randomized controlled double-blind clinical trial was conducted to evaluate tempe-based formulated foods fortreatment of young Indonesian children suffering from acute diarrhea. A total of 214 cases aged between 6 and 24 monthsvisiting two teaching hospitals, i.e., Sardjito hospital (n=102) in Yogyakarta and Karyadi hospital (n=112) in Semarang. Twocases from one hospital were dropped because they moved to other towns. In addition to their hospital food given duringhospitalization and daily food at home, 72 cases were given tempe-based formulated foods with tempe produced traditionally(group TT), 72 were given tempe produced industrially (group IT), whereas a control group of 68 received soybean powderformulated foods (group IS). Formula feedings were started immediately following WHO (world health organization) standardoral rehydration therapy (ORT) and continued at the patients homes for up to 90 consecutive days, including feedings duringhospitalization. Follow-up observations at patients homes were conducted twice weekly. The initial clinical characteristics ofthe cases in each group were similar. Using analysis of variance there was a non significant trend towards a shorter durationof diarrhea in the groups using tempe based formula (p=0.079). Using the t-test, the duration of diarrhea appeared to besignificantly shorter only for the group using formula with traditional tempe compared with the group using soy formula(p=0.035). The total amount of feeding formula and the total amount of calories consumed at the hospital and at home wassimilar for all three groups, although the group receiving the control formula consumed a somewhat higher amount of breastmilk (p=0.045) and a lower amount of solid food at home. Weight for age was below normal at the start of the study or afterrehydration (Z-score between -1.0 and -1.4) and approached the normal value at the end of the study for all three groups (Zscorebetween -0.51 and -0.27). The increase in Z-score was highest in the groups receiving tempe based formula (+1.0 inthe TT group and +0.9 in the IT group) and lowest in the IS group (+0.7). This implies that a tempe based formula can diminishthe duration of acute diarrhea and improve weight gain following an episode of acute diarrhea.